Drug therapy for double-hit lymphoma - Vania Phuoc; Jose Sandoval-Sus; Julio C Chavez (BioExcel Publishing Ltd, 2019)
Double-hit lymphoma (DHL) is a rare type of aggressive B-cell lymphoma defined as a high-grade B-cell lymphoma (HGBCL) with the presence of MYC, BCL2 and/or BCL6 rearrangements. Patients usually present with rapidly progressive and advanced stage of disease and, commonly, with extranodal involvement. Typically, patients become refractory to standard R-CHOP, and more aggressive regimens such as DA-EPOCH-R, R-hyperCVAD or CODOX-R regimens are typically needed. MYC is considered an "undruggable" mutation. Recent evidence suggests that pathogenic mechanisms associated with MYC could be potential targets. In this review, we also discuss the role of hematopoietic stem cell transplantation (HCT) and chimeric antigen receptor (CAR) T-cell therapy in DHL. We also discuss the role of potential novel agents such as BCL2 inhibitors, checkpoint inhibitors, bromodomain and extraterminal (BET) family inhibitors, Pi3K inhibitors, and others.